Emoções na perspectiva histórico-evolutiva de Charles Darwin - Romero, Frederico Ramalho (2023)
Under the theme of passions and emotions, this thesis aims to investigate the importance of Darwin's historical-evolutionary thinking in the reflection on the status of emotions. We sought to assess the influence of traditional philosophical theories of the passions in Darwin's thought using, as a methodology, the genealogical procedure of investigation and critical evaluation of the origin, background, and establishment of the concepts used over time. In the first chapter, we carried out a historical outline to review some of the main philosophical perspectives on passions and emotions, from the initial conceptions of Aristotle, Cicero and the Stoics, in the Ancient Age; passing through Augustine and Thomas Aquinas, in the Middle Ages; until the analyzes of Descartes and Hume, in the Modern Age. The second chapter was devoted to the analysis of passions and emotions in the context of Darwin's works, outlining the principles and concepts developed by the author, and how they contributed to the development of instincts and habits in man and other animals. In the third and final chapter, considerations were made about the similarities, connections, and differences between the presented theories, discussing how these philosophical theories influenced and shaped the development of Darwin's evolutionary theory. It was concluded that Darwin's theories revolutionized several traditional philosophical concepts of his time, including the acquisition of mental powers and capacities, of which emotions are a part. As a historical entity, Darwin's thought was strongly influenced by several personalities who preceded him and received the necessary help from many authors who worked later to eliminate inconsistencies and strengthen the foundations of his original hypotheses. From this historical-evolutionary perspective, Darwin's theories played an important role in the status of emotions, providing an explanation for their origin and development in man and animals, as well as other mental powers and capacities. Thus, the transfer of passions and emotions from the field of metaphysics to the field of science was definitively concluded.